The feet construction of 9-year-old children - Szczepanoska-Wołowiec, Beata; Sztandera, Paulina (Journal of Education, Health and Sport, 2018)
Introduction and purpose of the work, The human foot it is a very complex structure of the body, as it contains 26 bones, 19 muscles and 33 joints. Because of the cooperation all of those elements, the foot could fulfillthree basic functions such as load, amortization and locomotive functions. The aim of this research was to evaluate the feet construction in 9-year-old children from Masłów and Górno District.Material and method, The study involved 168 9-year-old children. There were 89 (53%) and boys 79 (47%) in the study group. The study was conducted in 2015/2016. The children were examined in schools after prior permission given by principals and parents or legal guardians. The body weight of the children was measured using the Tanita device and the body height was measured with the use of SECA. Then, the BMI index was calculated and compared to Centil grid presented in Olaf study. The plantar part of the foot was evaluated by 2D podoscanner. The relationship between the chosen parameters, sex and BMI was calculated. To examine the relationships, the author took advantage of nonparametric tests - Spearman’s rank correlation analysis, Manna-Whitneya-Wilcoxona test and χ2 test. When the level of statistical significance equaled p <0.05. Results. Almost half of the examined feet reached the values of Clark angle which are an evidence of lower arch or flat feet. Transverse flat feet occurred in 15% cases, hallux valgus angle α beyond the norm was examined in 8% of feet. There was no statistically significant relationship between BMI and Clark angle or hallux valgus angle α. Normal values of Clark angle occurred more often in girls’ feet. In the study group there was no statistically significant relationship between Wejsflog index,hallux valgus angle α and BMI.Conclusions In study group there is no statistically significant relationship between BMI and Clark angle. The girls in the study group more frequently had normal values of Clark angle. Wejsflog index is slightly higher in girls’ feet. Children with higher BMI have lower values of Wejsflog index, which is an evidence of lower longitudinal and transverse arch. In the study group there was no statistically significant relationship between BMI, sex and hallux valgus angle α.